Attitudes of Jordanian architecture students toward scientific research: A single-institution survey-based study. Issue 1 (31st December 2023) - Obeidat, Bushra; Obeidat, Laith M.
Abstract: Architecture is a profession in a perpetual state of change. Thus, it is essential for students to have a solid research foundation on which they can apply their knowledge and evidence-based solutions to architectural design, to enhance the quality of the built environment. Despite the fact that students' views and engagement in research have been receiving great attention recently, no studies have yet been conducted to assess Jordanian students' perspectives regarding scientific research. This paper examines the attitudes of a Jordanian university's architecture students toward scientific research. The descriptive study sampled 184 students from the College of Architecture who were asked to fill out a self-administered questionnaire. The data were both descriptively and quantitively analyzed using correlation, a Mann-Whitney U Test, and a Kruskal-Wallis Variance Test. The findings revealed that female students' outlook on research was more optimistic than that of male students. Moreover, fifth-year students had the least favorable opinions compared to third and fourth-year students. Furthermore, participants who followed architectural channels and broadcasts had more favorable sentiments toward research than those who did not. Finally, participants with previous experience in scientific research had fewer unfavorable opinions regarding research than those who were inexperienced. In conclusion, the majority of the students who participated in this study had positive attitudes toward scientific research. However, there is still a need to promote a culture of scientific research among undergraduate students, encouraging them to engage in scientific activities and providing them with opportunities to conduct research that will contribute to the architectural scene in Jordan.